Aspects of the theory of environmental policy in developing countries - Amitrajeet A. Batabyal; Hamid Beladi (Discrete Dynamics in Nature and Society)
We study two issues relating to the conduct of environmental policy in developing countries (DCs). First, when faced with a self-financing constraint, should an environmental authority (EA) raise/lower pollution taxes over time or should it run a deficit/surplus? Second, given recent findings about the dynamic inconsistency of optimal environmental policy, should an EA make its preferences about the relative benefits of environmental protection versus production public, or should it keep its preferences private? Our analysis reveals that when faced with a self-financing constraint, it is optimal for the EA to run a deficit/surplus. Second, social losses are lower when this EA keeps its preferences private.